Traversing the Waste Spectrum: Unveiling Pakistan's MSW Landscape and Solutions - Muhammad Asif; Mahmood Laghari; Azhar Abass; Mohammad Siddique; Abdulghaffaar Assayyidi Yusuf; Abdulhalim Musa Abubakar; Ahmed Abdo (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2023)
Municipal solid waste (MSW) management must be sustainable in order to meet the Sustainable Development Goals (SDGs) and address health, environmental, and disposal challenges caused by the vast amounts of trash generated. MSW management going wrong puts locals in danger. In Pakistan, the production of municipal solid trash is rising daily. Urban settlers and other organizations gather a lot of waste in various forms, usually defiling and making our surroundings uninviting. Due to the indiscriminate dumping of various wastes, the soil quality in the metropolitan area has decreased as a result of solid and liquefied waste disposal. Significant environmental concerns regarding soil and water pollution arise from transferring contaminated garbage and mixed fluid outside of waste disposal borders. The impacts of municipal garbage disposal on soil and water quality at open waste dumping sites were the main focus of this review. Using a soil and water quality index, in many regions of the world especially in regions where waste management practices are insufficient, the contamination of soil and water owing to incorrect municipal solid waste disposal is a serious environmental hazard. Open dumping, unregulated landfilling, and illegal dumping are examples of improper waste disposal practices that can result in pollution that affects the quality of the soil and water. They must also seek to identify sustainable waste management solutions. The effect of these emitted gaseous emissions has, however, been thoroughly researched. To safeguard the environment and public health, quick action must be made to control trace element pollution.